Enrolment of older adults with advanced or metastatic non-small cell lung cancer in first-line clinical trials in the multicentre ESME cohort. Issue 2 (March 2023) - Bringuier, Michael; Carton, Matthieu; Debieuvre, Didier; Pasquier, David; Perol, Maurice; Filleron, Thomas; Léna, Herve; Quantin, Xavier; Simon, Gaëtane; Baldini, Capucine
Abstract: Introduction: There is a great need for data based on clinical trials for the older population in order to improve treatment. Historically, the inclusion rate of older adults in clinical trials has been low, but the rate specific to lung cancer is unknown, as are the factors associated with enrolment. Materials and Methods: We used the national Epidemio-Strategy and Medical Economics Advanced or Metastatic Lung Cancer (AMLC) Data Platform, a multicentre real-life database. Inclusion criteria were patients with advanced or metastatic non-small cell lung cancer (AMNSCLC) aged 70 years or older, with at least one line of systemic treatment from 01 January 2015 to 31 December 2018. The primary objective was to evaluate the proportion of older adults enrolled in clinical trials. Secondary objectives were to identify factors associated with enrolment in clinical trials for older patients and to compare the overall survival of older adults included in trials versus those not included. Results: There were 3488 patients aged ≥70 years (median age at AMNSCLC 75 years). Among older patients, 234 (6.7%) were enrolled in a clinical trial in the first-line setting. Significant factors associated with enrolment in the multivariable analysis in older patients were: good Eastern Cooperative Oncology Group (ECOG) Performance Status (PS 0) ( p  < 0.001), de novo versus recurrent presentation at diagnosis (p < 0.001), and non-central nervous system (CNS) metastases versus advanced setting or CNS metastases (p < 0.001). Medical history was associated with fewer inclusions (odds ratio [OR] = 0.74, 95% confidence interval [CI] [0.56; 0.99]). Among older patients, being enrolled in a trial in the first-line setting was not associated with better overall survival (OS) (hazard ratio [HR] = 1.03; 95%CI 0.86–1.22) in the multivariable analysis. Discussion: In this large database, few older AMNSCLC patients were enrolled in a trial. Factors associated with enrolment were: good ECOG PS, absence of medical history, de novo AMNSCLC, and presentation with non-CNS metastases.